Sandy Soil Quality and Soybean Productivity in Medium-Duration Agricultural Production Systems † - Froio, Leonardo de Lima [UNESP]; Pechoto, Eduardo Augusto Pontes [UNESP]; Garruti, Moisés Vinícius Garcia [UNESP]; Soares, Deyvison de Asevedo; Sekiya, Bianca Midori Souza [UNESP]; Modesto, Viviane Cristina [UNESP]; Souza Júnior, Nelson Câmara de [UNESP]; Girardi, Vitória Almeida Moreira [UNESP]; Ribeiro, Naiane Antunes Alves [UNESP]; Matos, Aline Marchetti Silva [UNESP]; Lupatini, Gelci Carlos [UNESP]; Andreotti, Marcelo [UNESP] (MDPI, 2025)
The adoption of integrated production systems may be an alternative for improving soil health and increasing production. The aim of this study was to evaluate changes in soil fertility and microbial metabolism, as well as the impact on soybean productivity, in different conservation systems in contrast to the conventional system, after four years of adopting integrated systems. The experimental design used was a randomized block design with seven treatments and three replications. The treatments included different species of forage grasses, the no-tillage soybean–maize system in succession, and conventional planting. It was found that after four years of using integrated systems, the changes in soil health were small, indicating that these effects are seen over the long term. Soil chemistry showed that the use of forage grasses is essential for improving fertility, with a focus on phosphorus, potassium, magnesium, sulfur, base sum, and cation exchange capacity, which is reflected in the high soybean productivity in treatments with forage grasses, especially the use of Paiaguás and Piatã grasses. Even with slow changes in soil health, adopting integrated systems is an important practice for tropical sandy soils, as visible improvements in fertility were observed, which are reflected in productivity gains.
Keywords: forage grasses; no-tillage system; soil health